The Hedgehog signalling pathway in breast development, carcinogenesis and cancer therapy - Hui, Mun (BioMed Central, 2013)
Despite the progress achieved in breast cancer screening and therapeutic innovations, the basal-like subtype of breast cancer (BLBC) still represents a particular clinical challenge. In order to make an impact on survival in this type of aggressive breast cancer, new targeted therapeutic agents are urgently needed. Aberrant activation of the Hedgehog (Hh) signalling pathway has been unambiguously tied to cancer development and progression in a variety of solid malignancies, and the recent approval of vismodegib, an orally bioavailable small-molecule inhibitor of Smoothened, validates Hh signalling as a valuable therapeutic target. A number of recent publications have highlighted a role for Hh signalling in breast cancer models and clinical specimens. Interestingly, Hh ligand overexpression is associated with the BLBC phenotype and a poor outcome in terms of metastasis and breast cancer-related death. In this review, we provide a comprehensive overview of the canonical Hh signalling pathway in mammals, highlight its roles in mammary gland development and breast carcinogenesis and discuss its potential therapeutic value in BLBC.